'Granulitis': defining a common, biofilm-induced, hyperinflammatory wound pathology. (2nd January 2023) - Murphy, Christine A; Bowler, Philip G; Chowdhury, M Fahad
Abstract : The hard-to-heal (chronic) wound condition, now believed to be inextricably linked to the presence of microbial biofilm, has posed challenges in translating scientific understanding to clinical practice in recent decades. During this time, multiple descriptive terms of the wound pathology have been described, including critical colonisation, biofilm infection and inflammatory stasis. However, the absence of naming this disease state as a specifically identified condition that is tangible to treat has led to some confusion and delay in possible therapeutic approaches. When there is clinical uncertainty of wound status, antibiotics are too often inappropriately administered as a precaution. We therefore propose that introducing the term 'granulitis' (inflamed, unhealthy granulation tissue) could be used to identify the biofilm-induced, persistent inflammatory wound condition. This will help to raise clinician and public awareness of the condition, guide appropriate and prompt local wound hygiene, and encourage allocation of adequate resources to improve wound healing outcomes globally.